The profile of the graduate of the Administration Course and employability: a study in the Midwest region of Santa Catarina - De Oliveira, Melissa (2019)
This study aims to analyze if the skills and competences of the graduate profile of the course of administration are consistent with the profile demanded by companies and the work market. Relating the main items of the profile normalized by the national education council with technical demands of the profession and the business environment. The research approach is characterized as qualitative. Data were collected through access to electronic documents and interviews, with a semi-structured script. To analyze the data, we used the technique of content analysis through the categorization of variables, and use of the data triangulation strategy. The results delimit as the main competencies expected by the labor market: entrepreneurship, entrepreneurial behavior, leadership and systemic vision. It is believed that it is necessary to use active methodologies in the teaching-learning process, inserting practices that provide a closer approximation between academia and companies.